HUBUNGAN PENGETAHUAN DAN SIKAPHIGIENE SANITASIDENGANPRAKTIK HIGIENE SANITASI TENAGA PEMASAK MAKANAN DANMUTU BIOLOGI PADALAUK HEWANI DI RSUD KOTA SEMARANG - Ida Oktafiani; Heni Hendriyani (JURNAL RISET GIZI, 2015)
Background: Extraordinary events in 2011 caused 35 cases (28.69%), experienced food poisoning caused by microbes. Sanitation hygiene needs to be applied to maintain food quality, especially for cooking staff Objective: . This research was conducted to find out the relationship between knowledge and attitudes of sanitation hygiene with the practice of sanitation hygiene in cooking food and biological quality in animal side dishes in Semarang City General Hospital. Methods: Research included in institutional nutrition with a crossectional approach. The research sample used was animal dishes made from chicken meat, the respondents who were used as the research were food cookers. The data taken includes knowledge, attitudes and practices on cooking staff and biological quality on animal dishes using questionnaires, observation and laboratory checks. To find out the relationship between variables tested with Rank Spearman and Pearson Product Moment. Results: Animal side samples 58.3% had good biological quality, 100% good sanitation hygiene knowledge, respondents sanitation hygiene attitude 66.7% did not support, respondents sanitation hygiene practices 50% good. There is no relationship between knowledge and attitudes with hygiene sanitation practices (p = 0.712 and p = 0.614). There is a significant relationship between the variables of hygiene sanitation practices and total bacteria (r = -0.706) with p = 0.01. Conclusion : Good sanitation hygiene practices will reduce total bacteria in food and will produce good biological quality. It is recommended to increase supervision of sanitation hygiene practices.